Nuclear transformation of a dinoflagellate symbiont of corals - Gornik, Sebastian G.; Mägele, Ira; Hambleton, Elizabeth A.; Voss, Philipp A.; Waller, Ross F.; Guse, Annika (Frontiers in Marine Science, 2022)
Dinoflagellates are a diverse and ecologically important group of single-celled eukaryotes. Many are photosynthetic autotrophs while others are predatory, parasitic, or symbiotic. One major group — the Symbiodiniaceae — is well known for its role as coral symbionts that provide the coral host with vital nutrients. While genetic transformation protocols have been published for some non-symbiotic dinoflagellate species, robust methods for genetic manipulation of coral symbionts are lacking, hindering a detailed molecular understanding of this critical symbiotic interaction. Here, we describe the successful transformation of coral symbiont Breviolum minutum (strain SSB01). Using Golden Gate modular plasmid assembly and electroporation, we drove transient NLS-GFP expression from an endogenous dinoflagellate virus nuclear protein (DVNP) promoter and successfully targeted GFP to the dinoflagellate nucleus. We further determined that puromycin can efficiently select transformed cells using the puromycin N-acetyltransferase (pac) resistance gene. Transformed cells could be maintained under antibiotic selection for at least 12 months without losing resistance, albeit with slowly attenuating fluorescence signal. We thus tested the expression of hybrid GFP-2A-PAC polypeptides under the control of a single promoter sequence to overcome loss of fluorescence, but lack of efficient 2A cleavage seemingly hindered antibiotic selection interfering GFP function. Despite this, our transformation approach now allows unanswered questions of dinoflagellate biology to be addressed, as well as fundamental aspects of dinoflagellate-coral symbiosis.
Gesehen am 26.01.2023